Ag-catalyzed sulfonylation-peroxidation of alkenes with sulfonyl hydrazides and T-hydro. Issue 44 (31st October 2018) - Xu, Ran; Li, Zhiping
Graphical abstract: Highlights: The sulfonylation-peroxidation of alkenes is developed. β-Sulfonyl peroxides were synthesized by the three-component peroxidation of alkenes. β-Sulfonyl peroxides were converted into sulfone derivatives under mild conditions. Abstract: The sulfonylation-peroxidation of alkenes with sulfonyl hydrazides and T-hydro was developed. The Ag-catalyzed three-component peroxidation provides a method for synthesis of a variety of β-sulfonyl peroxides, which could be converted into various sulfone derivatives.